PENGARUH KEBUTUHAN KHALAYAK TERHADAP HASIL KREATIF PRODUKSI INI TALKSHOW NET TV - Arina Muntazah (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2020)
This study is aimed to investigate the individual needs towards the result of creative production of Ini Talkshow Net TV on resident of Jatirokeh Village, Brebes District, Central Java. Sub variabel of individual needs such as cognitive needs, affective needs, personal integrative needs, escapits needs. Sub variable of creative production such as continuity, composition, camera angle, punching line, gimmick, and clip hanger. This research belongs to quantitative research. Sample employed here is 78 resident of Jatirokeh Village, Brebes District, Central Java. In gathering the data, questionnaire is used and the result is counted by using likert scale. Moreover, to make the data valid, some tests are also used. They are validity test and reliability test. Furthermore, the data are analyzed by using double linier regression analysis. From the results of data analysis and discussion it was found that together the variables of individual needs (X1), have a significant effect on creative production (Y). The contribution of these variable amounted to 55,5% for individual needs, the remaining approximately influenced by other factors besides these variable.